Analisis Perbedaan Kebangkrutan dengan Metode Altman Z-Score, Grover dan Springate - Neneng Sudharyati; Arna Suryani; Indah Meilani (Universitas Batanghari Jambi, 2022)
This research was conducted on private cement companies and government cement companies listed on the Indonesia Stock Exchange during the period 2016-2021. The objectives of this study are (1) to find out and explain the calculation of bankruptcy analysis using the Altman Z-score, Springate and Grover (2) To find out and explain the ranking of financial conditions and categories in bankruptcy in cement companies using the Altman, Springate, and Grover methods (3) To find out and explain the analysis of differences in bankruptcy using the Altman Z-score, Springate and Grover. The test carried out in this study is the ANOVA difference test. Different tests to be able to see the calculation of bankruptcy with the Altman z- score, grover and springate methods. that the mean value of the Altman model is 4,2223, which is higher than the Springate model, which is 1.2090 and the Grover model is 0.8582. Tests on both financial distress prediction models show that the significance value is smaller than (0.0000 < 0.05). And shows a sig value of 0.000 and a statistical value of 6,719. The value of sig P value is 0.000 < 0.05. If the P value < the critical limit of 0.05, then there is a significant difference between the two group.